Traditional Herbal Medicine-Derived Sulforaphene LFS-01 Reverses Colitis in Mice by Selectively Altering the Gut Microbiota and Promoting Intestinal Gamma-Delta T Cells - Ming Li; Jiali Gao; Yan Tang; Meishuo Liu; Sijin Wu; Kunli Qu; Xiangyu Long; Huajun Li; Min Liu; Yinhui Liu; Jieli Yuan; Lei Mao; et al. (Frontiers Media S.A., 2018)
Sulforaphene (LFS-01) is a natural compound derived from traditional herbal medicine. Here, we show that oral administration of LFS-01 is able to dramatically alter the skewed gut microbiota and reverse colitis in model mice associated with an increase of intestinal γδT cells. Through 16S rDNA sequencing, we showed that LFS-01 can selectively suppress enteric pathogens such as Escherichia-Shigella and Helicobacter whereas the protective strains including Lactobacillus and Lachnospiraceae were significantly expanded after LFS-01 treatment. Interestingly, we demonstrated that LFS-01 administration can significantly promote the IL-17+γδT cells in model mice in response to the expanded Lactobacillus. We verified that the intracellular components of Lactobacillus can stimulate the growth of IL-17+γδT cells upon preincubation. The increased IL-17A after LFS-01 treatment in turn recovers the disrupted occludin subcellular location and protects the epithelial barrier in the colon of model mice. Remarkably, LFS-01 does not show apparent toxicity to animals and we demonstrated that LFS-01 also exerts strong protective effects in TNBS-induced colitis rats. Therefore, LFS-01 holds great promise for the treatment of inflammatory bowel disease (IBD) and warrants translation for use in clinical trials. Our work provided a new avenue for the treatment of IBD based on the strategy of harnessing intestinal symbiosis.